The Energy Networks Landscape. Impacts on Rural Land in the Molise Region - Cialdea, Donatella; Maccarone, Alessandra (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The paper concerns the study of the energy infrastructure that have the most impact on rural land. The analysis focuses on the systems for wind power and ground–mounted photovoltaic plants. The case study is the Region of Molise, in Southern Italy. This Region is an emblematic case because it has a significant number of installations as seen in relationship with the whole national territory. The case becomes even more special with reference to local guidelines that have undergone successive formulations, precisely in relation to the installation in specific areas of the Region. The study analyzes current national and regional rules and it proposes a methodology to support Local Authorities especially in relation to the definition of landscape quality aims, that the new Regional Landscape Plan must provide.